Blood Loss and Need for Transfusion in Percutaneous Nephrolithotomy (Bangladesh Journal of Urology, 2022)
Objective: To determine the amount of blood loss and need for blood transfusion in patients undergoing percutaneous nephrolithotomy (PCNL).Study Design: Observational study.Place and Duration of Study: National Institute of Kidney Diseases and Urology (NIKDU) and Popular Medical College Hospital, Dhaka from 2015 to 2019.Methodology: The percutaneous Nephrolithotomy data were retrospectively reviewed to identify patients with postoperative blood loss and need for blood transfusion. The amount of blood loss was estimated by the postoperative drop in hemoglobin factored by the quantity of blood transfusion. Various patients and procedure-related factors were assessed for association with total blood loss or blood transfusion requirement using stepwise univariate, forward multivariate regression analysis.Results: A total of 232 procedures were performed on 216 patients. Two hundred and thirty-two procedures were included in the study. There were 167 males and 65 females. The mean age was 41±14 years. The mean hemoglobin drop was 1.68 ± 1.3 gm/dL. The overall blood transfusion rate was 13.2%. Stepwise multivariate regression analysis showed that female gender (p = 0.003), stag-horn stone (p = 0.023), stone fragmentation with ultrasound (p = 0.054) and chronic renal failure (p = 0.001) were significantly predictive of the need for blood transfusion.Conclusion: Chronic renal failure, female gender, presence of staghorn calculi, and stone fragmentation using the ultrasonic device were predictive of blood transfusion in this cohort of patients.Bangladesh J. Urol. 2021; 24(2): 124-128